+0  
 
+1
342
1
avatar+231 

Evaluate:  \(\dfrac{(x+y)^2 - (x-y)^2}{y}\), for \(x=6\) and \(y \not= 0\).

 Mar 9, 2019
 #1
avatar+106533 
0

( x + y)^2  - (x - y)^2

_________________           factor the numerator as a difference of squares

              y 

 

[ ( x + y) + ( x - y) ] [ (x + y)  - (x - y) ]

_______________________________

                        y

 

[  2x] [ 2y ]

_________  =

        y

 

4x =

 

4(6)  =

 

24

 

 

cool cool cool

 Mar 9, 2019

16 Online Users

avatar